1990
DOI: 10.2307/2328672
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Stock Market Return Volatility During Overnight and Intraday Periods, 1964-1989

Abstract: This paper examines the variance of hourly market returns during . Results indicate that return volatility falls from the opening hour until early afternoon and rises thereafter and is significantly greater for intraday versus overnight periods. Market variance is also shown to change significantly over time, rising after NASDAQ began in 1971, rising after trading in stock options began in 1973, falling after fixed commissions were eliminated in 1975, rising after trading in stock index futures was introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 11 publications
4
38
0
Order By: Relevance
“…However, their finding was not confirmed by the subsequent study of Harris (1986) who analysed data of the same market, using a 15 minutes interval. Lockwood and Linn (1990) provided, also, support evidence of the findings of Wood et al (1985) by analyzing hourly prices of the DJ Index, for the period 1964-1969.…”
Section: Past Literaturesupporting
confidence: 83%
See 3 more Smart Citations
“…However, their finding was not confirmed by the subsequent study of Harris (1986) who analysed data of the same market, using a 15 minutes interval. Lockwood and Linn (1990) provided, also, support evidence of the findings of Wood et al (1985) by analyzing hourly prices of the DJ Index, for the period 1964-1969.…”
Section: Past Literaturesupporting
confidence: 83%
“…L-shaped patterns were, also, identified among others by Harris (1986), Deniz et al (2002), Lam and Tong (1999) and Tang and Lui (2002). On the contrary, Wood et al (1985), Harris (1986), Lockwood and Linn (1990), Werner and Kleidon (1996), Ozenbas, Schwartz and Wood (2002) suggested a U-shaped pattern for DAX.…”
Section: Intra-day Volatility Patternsmentioning
confidence: 75%
See 2 more Smart Citations
“…While inside the trading day, trading volume has remarkably declined. This U-shaped profile, according to Lee, Fok and Liu (2001), represents a global phenomenon, since several studies have revealed the presence of such intraday behavior as the works of Wood, McInish and Ord (1985), McInish and Wood (1990a), McInish and Wood (1992) and Lockwood and Linn (1990) respectively on the NYSE and the TSE. And the works of Chow, Lee, Liu (1994) and Liu (1994), Ho and Cheung (1991), as well as Ho Cheung and Cheung (1993) respectively on Taiwan stock market and SEHK.…”
Section: The Graphical Analysis Of Intraday Behavior Of the Trading Amentioning
confidence: 96%